Annotated catalog of the type specimens deposited at the fish collection of the universidade Estadual Paulista, Câmpus de São José do Rio Preto, São Paulo, Brazil (DZSJRP) - Andrade, Breno [UNESP]; Angulo, Arturo [UNESP]; Santos, Ana Cláudia [UNESP]; Cherobim, Arieli M. [UNESP]; Langeani, Francisco [UNESP] (Magnolia Press, 2017)
An annotated catalog of the type specimens deposited at the fish collection of the Universidade Estadual Paulista, Câmpus de São José do Rio Preto, São Paulo, Brazil (DZSJRP), is herein presented for consultation and scientific information. The type fish collection of the DZSJRP is comprised by 154 lots and 4,993 specimens, 18 of which are holotypes, and include a total of 53 species in six families. For each species, the following data are provided: current valid name, authority and year of description, type locality and holotype catalog number (for those lots hosted at the DZSJRP), and list of paratypes deposited at DZSJRP. For each lot the following data are provided: total number of specimens, standard length (SL; in mm), number of cleared and stained specimens, number of tissue samples, collection locality, elevation, geographical coordinates, collectors and collection date, when appropriate or available. Photos of holotypes deposited at DZSJRP are presented, showing the current conservation condition of the specimens.
Keywords: Freshwater fishes; Holotype; Neotropical region; Paratype